Economic Film “Pesantren Impian” Nadia Asma Works - Dia’ul Adha, Isna (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Ecranization is the process of transfering a novel into the film. Moving from novel to film inevitably leads to various changes. Therefore, ekranisasi can also be called a process of changesin form of reducing, adding, or changing with a number of variations. The Ecranization of Pesantren Impian film shows many reductions, additions, and changes. Pesantren Impian novel tells the story of a girl and her friends in seeking repentance by entering the Islamic boarding school. Whereas in the film tells the story of a girl and her friends who come to the Islamic boarding school to seek repentance which ends with serial killings that occur in the Dream Boarding School. The research method used by the researcher is descriptive qualitative narrative, it was found that there were several ecranizations that occurred in the plot, setting, and characterization in Pesantren Impian film